Attention, relevance, confidence, and satisfaction motivation model in mathematics education: a systematic literature review - Mengyao, He; Ismail, Zaleha; Ismail, Norulhuda; Xueting, He (International Journal of Evaluation and Research in Education (IJERE), 2025)
With the aims to find out how the attention, relevance, confidence, and satisfaction (ARCS) motivation model was applied into mathematics education; what research methods were used; and what outcomes were reported in these empirical studies, this paper systematically reviewed the empirical studies applied the ARCS motivation model into mathematics education trends on 2013-2023. Among 26 articles identified, the findings of this review indicated that the data from several contexts support the applicability of the ARCS model in diverse environments for mathematics learning, across different stages students, and in various nations. Three dimensions of the role of the ARCS model in mathematics education studies are identified: instructional design; theoretical framework; and measurement tool. Quantitative method was used most, and experimental studies and quasi-experimental studies were the main methods. Three types of outcomes were mainly focused on the past empirical studies: affective outcomes, cognitive outcomes, social outcomes. The findings highlighted the prospective paths that this area of research should pursue.